Design Thinking en la elaboración de políticas públicas: análisis del caso en Tame, Arauca - un Municipio PDET de Colombia - Amorocho, Carlos Julián (2025)
This case study focuses on the municipality of Tame, Arauca, where a public tourism policy was formulated using Design Thinking as a methodological tool. The process culminated in the presentation of a collective vision and a set of goals that will guide efforts over the next 10 years to position Tame as a leading tourist destination in the Eastern Plains. Three main milestones are highlighted: consolidating Tame as a benchmark in the department of Arauca; positioning it as the tourism epicenter of the Eastern Plains; and promoting it as a destination of national and international significance.